# Question: Powers of 2

## Comment on Powers of 2

### Can you also solve this

Can you also solve this question without factoring? If yes, could you explain how?
Kind regards, Lisa ### Hi Lisa,

Hi Lisa,
Sure, here's an approach that doesn't require factoring:
First evaluate the NUMERATOR:
2^(-13) - 2^(-9) = 1/(2^13) - 1/(2^9)
= 1/(2^13) - (2^4)/(2^13) [found common denominator]
= (1 - 2^4)/(2^13)

First evaluate the DENOMINATOR:
2^(-13) - 2^(-17) = 1/(2^13) - 1/(2^17)
= (2^4)/(2^17) - 1/(2^17) [found common denominator]
= (2^4 - 1)/(2^17)

So, NUMERATOR/DENOMINATOR = [(1 - 2^4)/(2^13) ]/[(2^4 - 1)/(2^17)]
= [(1 - 2^4)(2^17)]/[(2^4 - 1)/(2^13)]
Now recognize that (1 - 2^4)/(2^4 - 1) = -1
So, our fraction = -[(2^17)/(2^13)]
= -(2^4)
= -16

### Hi Brent,

Hi Brent,
Thank you for the help here.
In my shortcut search as usual, I followed your idea of "something" again.
I noticed that the numerator would be a negative "SOMETHING" while the denominator would be positive "something" so the answer has to be "something" that is negative and greater than 1. Only A fit. ### Perfect reasoning! Great

Perfect reasoning! Great shortcut!!

### Hi Brent, I am lost about

Hi Brent, I am lost about something that could be negative and greater than 1.
Could you guide me where I am wrong? ### Great question, Esguitar!

Great question, Esguitar!

I should have clarified abrahamic01's original comment so as not to confuse others.

I believe abrahamic01 meant so say that the MAGNITUDE (aka absolute value) of the correct answer is greater than 1.

In that sense, -16 has a magnitude that's greater than 1

Does that help?

Cheers,
Brent

### Hello,

Hello,
I just want to point out that once both the numerator and denominator is factored, there is no need to actually calculate (1 - 2^4) / (2^4 - 1) under the general rule that (x-y)/(y-x) always = -1, so we can just calculate 2^4 * -1 = -16. ### Good point.

Good point.
That would save us the step where we got (-15)/15 = -1

Cheers,
Brent